2016
DOI: 10.1002/pros.23161
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated induction of cell survival signaling in the inflamed microenvironment of the prostate

Abstract: The prostate responds to deleterious inflammation with induction of cell survival mechanisms, most notably survivin and autophagy, demonstrating a coordinated induction of survival factors that protects and expands a specialized set of prostatic epithelial cells as part of the repair and recovery process during inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…As part of the CPC, survivin along with members Borealin, INCENP and Aurora B kinase orient the chromosomes during mitosis. Previously, our lab has demonstrated that survivin is juxtaposed to inflammation in human prostate cancer specimens and may play a role in repair and recovery of prostatic tissue [ 30 ]. Attempts at directly targeting survivin have ultimately failed in clinic, therefore new approaches or therapeutics that in some way block the expression or function of survivin are needed.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the CPC, survivin along with members Borealin, INCENP and Aurora B kinase orient the chromosomes during mitosis. Previously, our lab has demonstrated that survivin is juxtaposed to inflammation in human prostate cancer specimens and may play a role in repair and recovery of prostatic tissue [ 30 ]. Attempts at directly targeting survivin have ultimately failed in clinic, therefore new approaches or therapeutics that in some way block the expression or function of survivin are needed.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation to increase the survival prospects of prostate epithelium against harmful factors, the synthesis of a variety of factors increases led by growth factors. Thus the hyperproliferative environment developing in prostate tissue forms an appropriate environment for cancer formation [15].…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were fixed at room temperature overnight in 10% neutral buffered formalin, and processed routinely through ethanol into xylene. Processed tissues were embedded in paraffin and cut on a microtome into 5-mm sections, mounted on positively charged slides, and baked at 60 C. Sections from the CisRef-TMA were stained with the APE1/Ref-1 antibody by the Indiana IF and IHC IF protocols were followed as described previously (31). Sections were processed routinely and subjected to heatinduced antigen retrieval in 10 mmol/L citrate buffer.…”
Section: Human Specimensmentioning
confidence: 99%
“…Sections were blocked at ambient temperature with a BSA-Donkey serum blocking medium for 2-4 hours, and incubated with the same blocking medium containing the indicated primary antibodies overnight at 4 C. Primary antibodies and dilutions included rabbit survivin (1:100, Cell Signaling Technology), mouse APE1/Ref-1 (1:200, Novus Biologicals), rabbit BrdU (1:200, Cell Signaling Technology), and mouse PanCK (1:200, Cell Signaling Technology). After incubation, all sections were washed with 1Â PBS-Tween and incubated with blocking medium containing with the species-specific (Invitrogen) IgG Alexa 488 and IgG Alexa 594-conjugated secondary antibody targeting rabbit or mouse for 1 hour at room tem-perature at a dilution of 1:200 as optimized previously (31). Nuclei were stained by incubation with Hoechst 33258 Nuclear Stain (Sigma) at a concentration of 1 mg/mL.…”
Section: Human Specimensmentioning
confidence: 99%